Aspek Perencanaan Bisnis Batik Tanah Liek - Septri Anisa (Dharma Ekonomi, 2025)
Batik Tanah Liek is one form of Minangkabau cultural heritage that has a unique coloring process that uses natural materials in the form of clay. This study aims to analyze the business planning of Batik Tanah Liek from two main aspects, namely marketing and finance. The method used is a descriptive approach with secondary data and a five-year financial projection simulation. The marketing strategy is focused on cost-based pricing and digital promotion through social media, participation in cultural events, and partnerships with local business actors. Financial analysis includes profit and loss projections, cash flow, and break-even point (BEP) analysis. The results show that the strategy developed is able to provide significant profit growth potential and healthy cash flow. These findings indicate that Batik Tanah Liek has the potential to develop as a competitive and sustainable local fashion brand.